A influência do ativismo jurídico transnacional na elaboração de normas e políticas públicas no Brasil: uma análise dos casos brasileiros no sistema interamericano de direitos humanos - Barrozo, Rebecca Paradellas (2017)
Transnational legal activism is the engagement in international courts or quasi-judicial institutions to strengthen the demands of social movements, to constrain States to comply with human rights norms and to promote legal and political change within countries (SANTOS, 2007). The Inter-American System of Human Rights allows this proceeding through the system of denunciations in the Inter-American Commission on Human Rights. Through the example of the work of activism organizations in denouncing violations of rights committed (or omitted) by the Brazilian State in the Inter-American system of human rights, the objective of this work is to carry out an empirical analysis about the fruits conquered by (national and international) human rights NGOs with regards to the creation of norms and public policies in national territory, due to its work in the Inter-American Commission.